2014
DOI: 10.1021/es5021058
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Impacts Soil Microbial Community Composition and Nitrogen Cycling in an Acidic Soil Planted with Rape

Abstract: Biochar has been suggested to improve acidic soils and to mitigate greenhouse gas emissions. However, little has been done on the role of biochar in ameliorating acidified soils induced by overuse of nitrogen fertilizers. In this study, we designed a pot trial with an acidic soil (pH 4.48) in a greenhouse to study the interconnections between microbial community, soil chemical property changes, and N 2 O emissions after biochar application. The results showed that biochar increased plant growth, soil pH, total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
170
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 421 publications
(204 citation statements)
references
References 62 publications
11
170
5
Order By: Relevance
“…Total organic carbon (TOC) was determined with a TOC analyzer (Shimadzu TOC-Vcph, Japan) with a solid sample module (SSM-5000A), and C, N, and S with an elemental analyzer (Vario MAX CNS, Germany). Extractable major and trace metal concentrations were digested using a strong acid digestion method 25 and measured with inductively coupled plasma optical emission spectrometry (ICP-OES; Optima, 7000DV; PerkinElmer) and inductively coupled plasma mass spectrometry (ICP-MS; 7500cx; Agilent Technologies, Inc., Tokyo, Japan).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Total organic carbon (TOC) was determined with a TOC analyzer (Shimadzu TOC-Vcph, Japan) with a solid sample module (SSM-5000A), and C, N, and S with an elemental analyzer (Vario MAX CNS, Germany). Extractable major and trace metal concentrations were digested using a strong acid digestion method 25 and measured with inductively coupled plasma optical emission spectrometry (ICP-OES; Optima, 7000DV; PerkinElmer) and inductively coupled plasma mass spectrometry (ICP-MS; 7500cx; Agilent Technologies, Inc., Tokyo, Japan).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…For example, Gemmatimonadetes have been found to decrease in relative abundance with the addition of wheat residues (Bernard et al, 2007), were more active in soil microcosms that did not receive leaf litter (Pfeiffer et al, 2013), and were more likely to be decomposing existing SOM than fresh OM (Pascault et al, 2013). Of particular relevance, Gemmatimonadetes increased with the addition of rice straw PyOM made at 500°C to a farmed Acrisol in a pot trial (Xu et al, 2014). This increase was driven by increases from the class Gemmatimonadetes, with some Gemm-1 and Gemm-3 increasing in relative abundance as well.…”
Section: Pyom Effects On the Soil Bacterial Communitymentioning
confidence: 99%
“…For example, significant differences were found between soil bacterial communities in Amazonian Dark Earth soils (amended with PyOM thousands of years ago), PyOM isolated from the Amazonian Dark Earth soils and adjacent unamended Acrisols, by surveying small subunit ribosomal RNA (SSU rRNA) genes (Taketani et al, 2013). A handful of other studies have used high-throughput sequencing approaches to characterize PyOM effects on soil bacterial community composition (for example, Nielsen et al, 2014;Xu et al, 2014). However, owing to the low number of studies and the wide diversity of PyOM materials, addition rates, soils and environmental conditions, it is difficult to draw generalizable conclusions about the effects of PyOM on soil microbial community composition, particularly at the level of individual taxa.…”
Section: Introductionmentioning
confidence: 99%
“…All these studies suggested that SOM cycling might be influenced via microorganisms after BC addition. A number of studies reported changes in the microbial community after BC addition that were attributed to the physico-chemical properties of BC (e.g., aeration, sorption), as well as BC-induced changes in soil properties such as pH (Gul et al, 2015;Jindo et al, 2012;Rillig et al, 2010;Xu et al, 2014). However, information on microbial communities associated with soil SOM dynamics related to BC amendment is particularly limited (Gul et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, information on microbial communities associated with soil SOM dynamics related to BC amendment is particularly limited (Gul et al, 2015). Furthermore, the majority of BC studies have relied on short-time incubation experiments (Farrell et al, 2013;Pietikäinen et al, 2000;Xu et al, 2014). Long-term field trials examining organic C-and N-related effects of BC on microorganisms still remain to be studied.…”
Section: Introductionmentioning
confidence: 99%